Preparing faculty for problem-based learning curriculum at Patan Academy of Health Sciences, Nepal - Upadhyay, Shambhu Kumar; Bhandary, Shital; Ghimire, Satish Raj; Maharjan, Babu Raja; Shrestha, Ira; Joshi, Mili; Vaidya, Sujan (Journal of Patan Academy of Health Sciences, 2015)
Introduction: Patan Academy of Health Sciences (PAHS) in Nepal has adopted problem-based learning (PBL) as principal pedagogy to foster attributes predefined for its medical graduates. This study evaluates reaction of participants in PBL tutor-training program focused on PBL process and its assessment. Methods: An orientation program was organized separately for 24 faculty members and 45 higher secondary science majoring students prior to conduction of real-time PBL tutorial sessions. Faculty’s reaction as PBL tutors was collected before and after the orientation program using a 13- item self-administered questionnaire. Internal consistency reliability of the questionnaire items and outcome of the training program were assessed using Cronbach’s alpha, coefficient of variation, Shapiro-Wilk test, paired t-test and adjusted effect size for dependent samples. Results: The pre-test internal consistency reliability was high (0.89) whereas it was acceptable (0.69) for post-test. The average score increased from 26.50 to 34.55 and standard deviation decreased from 5.39 to 2.70 between pre- and post-test. Difference between post- and pre-tests total scores followed normal distribution and suitable parametric test (paired t-test) revealed the difference was highly significant (p< 0.0001). The adjusted effect size was high (1.65) for small dependent samples. Conclusions: The faculty training for PBL and assessment was helpful in implementing PBL pedagogy at PAHS. Journal of Patan Academy of Health Sciences, Vol. 2, No. 1, 2015. page: 30-34